Using the Consolidated Framework for Implementation Research (CFIR) to evaluate implementation effectiveness of a facilitated approach to an asthma shared decision making intervention. (3rd April 2021) - Shade, Lindsay; Ludden, Thomas; Dolor, Rowena J.; Halladay, Jacqueline; Reeves, Kelly; Rees, Jennifer; Hendrickson, Lori; Bray, Paul; Tapp, Hazel
Abstract: Objective: To describe the evaluation of implementation effectiveness of an asthma shared decision making (SDM) intervention at the 10 individual facilitator-led primary care practices in the ADAPT-NC Study using the Consolidated Framework for Implementation Research (CFIR). Methods: Practices were scored across 40 CFIR constructs within 5 domains using a previously published scoring system of -2 to +2. Based on overall construct scores, practices were then classified as high, medium, or low adopters. To evaluate clinical outcomes, changes in asthma exacerbations were assessed for emergency department (ED) visits, hospitalizations, and oral steroid prescription orders. Using regression analysis, the absolute change in percent for each outcome relative to the CFIR score for each practice was analyzed. (Trial registration #NCT02047929). Results: Implementation effectiveness was reflected in CFIR score differences with 7 high, 1 medium, and 2 low adopter practices. High adopters mostly scored well across all domains. Weaknesses were consistent amongst the 2 low adopters with lower scores in the Inner Setting, Characteristics of Individuals, and Process domains. While no significant correlations were seen between the practices' CFIR scores and the absolute change in ED visits, hospitalizations, or oral steroid prescription orders, practices with higher percentages of children had greater improvements in clinical outcomes. Conclusions: The CFIR was used to evaluate the asthma SDM intervention implementation at 10 facilitator-led practices. While there was no significant correlation between higher implementation effectiveness and greater improvement in clinical outcomes, practices with a higher proportion of pediatric patients did experience a significant reduction in overall exacerbations post-implementation.